APAKAH SPIRITUAL LEADERSHIP MENYEBABKAN HAPPINESS AT WORK PADA KARYAWAN BANK BUMN? - Raidah Sitti Suciani; Dita Oki Berlyanti; Wiwik Robiatul Adawiyah (Business, Economics dan Entrepreneurship, 2023)
This study aims to analyze the influence of Spiritual Leadership, Transformational Leadership, on Happiness at Work. The sampling method used was purposive sampling with 61 employees of Bank Persero Cibinong, Bogor Regency. The data analysis technique in this study used a test technique instrument using multiple linear regression. The results of this study indicate that Spiritual Leadership and Transformational Leadership have a positive effect on Happiness at Work. The managerial implications of this research are that leaders in organizations apply Spiritual Leadership, so that employees are happier at work